Skills and their impact on labor market performance using European cross-country evidence - GIOTIS, GEORGIOS (International Journal of Language, Translation and Intercultural Communication, 2018)
The impact of skills on labor market performance is a topic which has attracted a growing attention during the last years and has become a major concern among policy makers. In this paper, I discuss on the skill needs in Europe and skill shortages and surpluses as well. Moreover, I examine five important dimensions of skills: information skills, communication skills, problem solving skills, software skills and digital skills. For all of them I have found negative correlation with unemployment rates, findings which suggest that these skills can improve the employment prospects and reduce the skill mismatch in the workplace. Finally, I estimate the effect of three levels of education on unemployment rates across a sample of 28 European countries for the 1999-2016 time period. Both tertiary and elementary education seem to reduce unemployment for European countries, while secondary education is connected with increased unemployment rates.